The Influence of Social Capital Domains on Self-Rated Health Among Serbian High-School Students? A School-Based Cross-Sectional Study - Dario Novak; Ivana Milanovic; Snezana Radisavljevic Janic; Lovro Štefan; Tomislav Kristicevic (Montenegrin Sports Academy, 2016)
Social capital has been shown as a positive asset for improving overall health in children and youth. Thus, the purpose of the present study was to determine the associations between family, neighborhood and school social capital with self-rated health among Serbian high-school students. This cross-sectional study on 1220 high-school students (539 males and 681 females) was carried out in the school year 2015/2016. Main outcome was defined as self-rated health, measured by one question: "How would you rate your health?" with five possible answers: (1) very poor; (2) poor, (3) fair, (4) good and (5) excellent. We binarised the outcome, where answers "very poor", "poor" and "fair" represented "poor health" and "good" and "excellent" "good health". Multiple logistic regression was used to determine the associations between social capital domains and self-rated health. Adjusted by gender, body-mass index, self-perceived socioeconomic status, psychological distress and physical activity, good self-rated health was positively associated only with high family social capital (OR 2.29; 95% CI 1.62 to 3.24). When all the social capital variables were entered simultaneously, self-rated health remained associated with family social capital (OR 2.28; 95% CI 1.61 to 3.24). Family social capital was the only domain strongly associated with self-rated health. Since neighborhood and school social capital represent key support and empathy for children and youth, neighborhood and school-based strategies and policies should be implemented within the system to increase overall physical and mental health.